Effectiveness of riverbank filtration system in removal of organic contaminants from Sg.Belat river using activated carbon : a laboratory testing - Wan Zafira Afiqah, Wan Hanafi (2014)
Riverbank filtration (RBF) is a water treatment technology that consists of an extraction well installed adjacent to an alluvial aquifer. This aquifer, acts as a filtration medium for filtering contaminants from the extracted water. During the underground passage, a series of physical, chemical, and biological process take place, improving the quality of the surface water, substituting or reducing conventional drinking water treatment. The use of RBF, which utilizes the riverbank for extraction and filtration of rivers, may be considered as a cheaper alternative. RBF system have been shown to effectively remove pollutants such as, particulate matters, organic compounds, microbes and a large number of chemical micro pollutants. Activated carbon (AC) adsorption has long being recognised as one of the most effective technologies at removing natural organic matter from water in drinking water treatment plants. In this study the effectiveness of using activated carbon as a filtration media when it mixed with natural soil are analyzed. Apart from that, the water quality parameters were tested to compare the value of before and after filtration process. The results for the percentages removal of the parameter in terms of water quality for nature soil are: BOD 5 at 20°C 10%; COD 81%; TOC 0%; Total nitrogen 0 %; Total phosphorus 63 % while the percentages removal of the parameter in terms of water quality for nature soil + AC are: BOD 5 at 20°C 5%; COD 100%; TOC 0%; Total nitrogen 0%; Total phosphorus 49%. Although not all the value of parameter was decreases but some of parameter do decreases in value which it can be considered that the water become clean than before undergoes filtration process. The design of this experiment clearly shows that modification of soil by mixing AC can be used as filtration media in RBF system.